Особливості організації fronthaul у централізованій архітектурі мобільної мережі - Акіменко, А. С.; Ворончихін, О. А. (ХНУРЕ, 2023)
An analysis of the concept of centralized baseband processing in the LTE mobile network has been carried out. It was found that when using a centralized scenario, maintenance and modernization are simplified. This concept requires an expensive FH network, but with lower requirements. This is related to the distribution and processing of signals of the physical layer in the mobile network BS. Options for solving the FH problem are considered, taking into account the centralization of RAN functions.